Ruminal fermentation characteristics and related feeding values of compound feeds and their constituting single feeds studied by using in vitro techniques. (8th September 2020) - Grubješić, G.; Titze, N.; Krieg, J.; Rodehutscord, M.
Abstract : Single concentrate feeds are mixed together forming compound feeds for cattle. However, knowledge regarding the potential interactions (associative effects) between the feeding values of single feeds in compound feeds is lacking. The main objective of the present study was to evaluate ruminal fermentation characteristics and feeding values of eight industrially produced compound feeds in mash form from their constituent single feeds for dairy cows through in vitro assays. Additivity was given for gas production (GP ), digestibility of organic matter (dOM ) and utilisable CP at the duodenum (uCP ). Additivity of CP fractions (determined using the Cornell Net Carbohydrate and Protein System (CNCPS )) was dependent on the fraction and compound feed type; however, the effective degradation calculated from CP fractions (ED CNCPS ) showed additivity. Additivity was not given for intestinal digestibility of rumen-undegraded protein (ID RUP ) for five out of eight compound feeds. Precise calculation of metabolisable energy (ME ) of compound feeds from ME of single feeds was possible when using the same ME equations for all single and compound feeds. Compound feeds are often provided in pellet form; therefore, our second objective was to evaluate the effects of pelleting on ruminal fermentation characteristics and feeding values of compound feeds. Pelleting affected GP at 24 h (GP 24 ; up to 2.4 ml/200 mg DM), dOM (up to 2.3 percentage point (pp )) and ME (up to 0.3 MJ/kg DM), but these differences were overall small. More considerable effects of pelleting were observed for uCP, which was increased in all compound feeds except the two with the highest CP concentrations. The IDRUP was lower in most compound feeds following pelleting (up to 15 pp). Pelleting also affected CP fractions in a non-systematic way. Overall, the effects of pelleting were not considerable, which could be because pelleting conditions were mild. Our third objective was to compare in situ ruminal CP degradation (ED IN_SITU ) of compound feeds with ED using two prediction methods based on CP fractions. EDIN_SITU reference data were obtained from a companion study using the same feeds. Prediction accuracy of EDIN_SITU and EDCNCPS was variable and depended on the compound feed and prediction method. However, future studies are needed as to date not enough data are published to draw overall conclusions for the prediction of EDIN_SITU from CP fractions.